ChemInform Abstract: A New Efficient Stereoselective Method for the Synthesis of (E)‐5‐Aminoallyl‐pyrimidine‐5′‐triphosphates Using Palladium‐Catalyzed Heck Reaction. Issue 27 (18th June 2015) - Kore, Anilkumar R.; Senthilvelan, Annamalai; Shanmugasundaram, Muthian; Sandoval, David; Pardo, Andrew
Abstract The catalytic reaction tolerates a wide variety of functional groups such as hydroxyl, amide, phosphorus, and amine present in the substrates.